Kommunitaristischer Liberalismus: Der Text basiert auf einer Vorlesung, die am 12.4.1994 am Woodrow Wilson International Center for Scholars, Washington, D. C., gehalten wurde - Selznick, Philip (Der Staat, 1995)
This essay offers a fresh perspective on the "communitarian-liberal" debate. Instead of attacking purported premises of liberalism, such as "atomism", Selznick calls for a union of communitarian and liberal perspectives. The article examines three basic liberal ideals: equality, liberty, rationality. These are warmly embraced, but they are also criticized as having been corrupted by overly abstract, absolutist, uncontextual modes of thought. These criticisms are communitarian because they give great weight to the social frameworks within which all ideals find their limits as well as their opportunities. In addition, the article expresses communitarian resistance to liberal doctrines that dilute the idea of a "common good", and that treat democracy as mainly a device for managing diversity. On the contrary, it is argued, we need a robust conception of the general welfare; and democracy should be understood as a way of bringing people together to solve common problems, not as mainly a way of keeping them from one another's throats. (Der Staat / FUB)